1999
DOI: 10.4141/s98-050
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient losses to soil from field storage of solid poultry manure

Abstract: . Nutrient losses to soil from field storage of solid poultry manure. Can. J. Soil Sci. 79: 183-189. The study was done to quantify the effect of uncovered field storage of solid poultry manure in south coastal British Columbia on a site where solid turkey manure was stored uncovered each fall and winter for approximately 6 yr. The soil was sampled to 370 cm depth in a transect with six sampling locations: two in the manure storage area, and two on either side of the manure storage area. The soil was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Compared to the control plots at the end of the study there were small but significant increases in soil nitrate concentration occurred under both the covered and enveloped field heaps, namely at the 60-90 cm depth under both the covered and enveloped treatments, and at the 0-30 cm depth under the enveloped plots. As these increases took place under enveloped heaps it is difficult to see how they reflect direct leaching of nutrients from the litter as previously reported by Zebarth et al (1999) following winter storage of poultry litter in uncovered field heaps over a 6 year period.…”
Section: Discussionmentioning
confidence: 91%
“…Compared to the control plots at the end of the study there were small but significant increases in soil nitrate concentration occurred under both the covered and enveloped field heaps, namely at the 60-90 cm depth under both the covered and enveloped treatments, and at the 0-30 cm depth under the enveloped plots. As these increases took place under enveloped heaps it is difficult to see how they reflect direct leaching of nutrients from the litter as previously reported by Zebarth et al (1999) following winter storage of poultry litter in uncovered field heaps over a 6 year period.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Doody et al (2012a) found no significant increase in soil P concentrations between 0 and 15 cm in the soil profile beneath covered poultry litter heaps after 90 days of storage. However, the sizes of the heaps in the study of Doody et al (2012a) were much smaller than those used by Frame et al (2007) and Zebarth et al (1999).…”
Section: Phosphorusmentioning
confidence: 68%
“…However, Frame et al (2007) reported a large increase in soil P beneath the turkey litter heaps increasing from <50 ppm to >150 ppm in the top 15 cm of the soil profile. Similarly Zebarth et al (1999) reported that there was a significant increase in extractable soil P concentrations to a depth of 180 cm in the soil profile under an uncovered poultry litter heap. In contrast, Doody et al (2012a) found no significant increase in soil P concentrations between 0 and 15 cm in the soil profile beneath covered poultry litter heaps after 90 days of storage.…”
Section: Phosphorusmentioning
confidence: 96%
“…fertilizer band were measured only for 0-15 cm depth, whereas this pattern was measured throughout the root zone at some sites for soil test K. Similarly, Zebarth et al (1999b) found greater downward movement of K than of P where solid manure had been stored in field stockpiles. The random sampling strategy gives unbiased estimates of soil inorganic N and soil test P and K. However, the number of cores required to obtain a given precision for a given probability level are generally greater for the random than for the systematic sampling strategies.…”
Section: Discussionmentioning
confidence: 84%